1995
DOI: 10.1002/bjs.1800821024
|View full text |Cite
|
Sign up to set email alerts
|

Optimum method for urinary drainage in major abdominal surgery: A prospective randomized trial of suprapubic versus urethral catheterization

Abstract: The outcome of suprapubic and urethral catheterization in abdominal surgery was compared in a prospective randomized trial. Twenty-eight patients received a suprapubic and 29 a urethral catheter. The groups were similar in terms of age, sex, operation performed and postoperative analgesia. There was no difference in the duration of catheterization (suprapubic: median 5 (range 4-10) days; urethral: median 4 (range 2-11) days). Urinary sepsis occurred in three patients in each group. Urethral catheters caused pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…In the present study, a higher relative risk of 3.4 (95% CI = 1.4–8.0) for development of infection was found in patients with a catheter for more than 7 days, but this could also be influenced by a higher number of postoperative complications and recatheterization in this group of patients. A sex-related difference in infection rate as found in this study has been mentioned earlier [3, 4, 5, 6, 7, 8]. Sethia et al [3]did not find a difference between urethral and suprapubic catheter infection rates in men, but a significant lower infection rate in women with a suprapubic catheter.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the present study, a higher relative risk of 3.4 (95% CI = 1.4–8.0) for development of infection was found in patients with a catheter for more than 7 days, but this could also be influenced by a higher number of postoperative complications and recatheterization in this group of patients. A sex-related difference in infection rate as found in this study has been mentioned earlier [3, 4, 5, 6, 7, 8]. Sethia et al [3]did not find a difference between urethral and suprapubic catheter infection rates in men, but a significant lower infection rate in women with a suprapubic catheter.…”
Section: Discussionsupporting
confidence: 52%
“…The disadvantages are the higher costs of the catheter and the more difficult catheterization technique which is not feasible under all circumstances. The effects of the two catheter systems on the development of urinary tract infections have only been studied in a few and relative small randomized studies with limited power [3, 4, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…18,27 In our study, bladder washout represents a very high risk of ESBL infection in both univariate (p<0.001) and multivariate analysis (p<0.001). This can be explained by the manipulation of the system, the increase of the catheterization time, and the duration of hospitalization.…”
Section: Closed Drainagementioning
confidence: 55%
“…Studies examining postoperative urinary tract infections report incidences from 4 to 60% [1,3,4,5,8,9,10,11,13,15]. Several randomized controlled trials concluded suprapubic catheters to be superior to transurethral catheters for postoperative urinary drainage in order to reduce rates of urinary tract infection [1,5,9,10,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the two catheter systems on the risk of postoperative urinary retention and increased PRVs have only been studied in a few randomized controlled trials. The majority of these trials has been performed in patients, both men and women, who underwent general abdominal surgery [8,9,10,11,12]. A small number of trials studied women after gynecological surgery, concerning procedures such as correction of stress incontinence, radical hysterectomy for cervical carcinoma and a combination of various pelvic organ prolapse surgery techniques [1,13,14].…”
Section: Discussionmentioning
confidence: 99%